The impact of differing audience sizes on referees and team performance from a North American perspective. (May 2022) - Szabó, Dávid Zoltán
Abstract: The COVID-19 pandemic provides a natural experimental framework to comprehensively test the effect of crowds on both referees and players. We examine this from a North American perspective, using data from three major leagues: the National Basketball Association (NBA), National Football League (NFL) and National Hockey League (NHL). In all three leagues in the 2020–2021 season, matches were played either in empty stadiums or before diverse audience sizes. We find that the lockdown affects NBA and NFL results, by lowering the prospects of winning and the expected scoring points of the home team, when games are played without an audience. Conversely, the lockdown does not substantially influence the outcomes of NHL games. We also examine the effect of audience size on game outcomes using historical observations from the past decade, when no lockdown measures were in force. Interestingly, a larger audience size increases the chance of winning and the expected scoring points of the visiting team for NFL games. No significant effect of the audience size on match outcomes is observed for NBA or NHL games. Regarding referee decisions, spectators do not significantly influence referee calls of NHL matches. As for NBA and NFL, the lockdown significantly increases the total number of referee calls but does not prompt more biased decisions towards either of the teams. Finally, a larger audience leads to referee calls more favourable to the visiting team for NFL games. These results extend the literature regarding crowd pressure on the behaviour of players and officials, with an indication that the specific sports activity has a pivotal role in the response to a cheering audience. Highlights: Referees' decisions and teams' performances of North American leagues for Pre- and Post-COVID-19 period are examined. Lockdown deteriorates the performance of the home NBA and NFL teams, but does not affect the performance of NHL teams. Lockdown does not affect referee bias, but spectators have an impact on referees' decisions for NFL and NBA matches.